A Study of the Mechanism of the y-Elimination Reaction of 3-Phenylpropyltrimethylammonium Iodide - Westaway, Kenneth (My University, 1968)
Deuterium tracer studies, kinetic isotope effect measurements and product composition studies in both ammonia and ammonia-d3 have been used to elucidate the mechanism of the y-elimination reaction of 3-phenylpropyltrimethylammonium iodide with potassium amide in liquid ammonia at -55°. Deuterium tracer studies involving the products from the reaction of 3,3-dideutero-3-phenylpropyltrimethylammonium iodide have excluded the carbene and ylide mechanism. A deuterium exchange test involving the deuterated quaternary salt in ammonia demonstrated that a y-carbanion is formed during the reaction. In addition, a large y-hydrogen isotope effect (kH/kD > 22) and a large nitrogen isotope effect (k^14/K^15 = 1.022) were observed for the reaction. These results are consistent with either an Elcb mechanism in which the rates of ring closure and of return of the carbanion are of comparable magnitudes or a concerted mechanism accompanied by an irrelevant exchange reaction at the y-carbon. The latter has been eliminated on the basis of a deuterium exchange test involving the undeuterated quaternary salt in ammonia-d3 and the relative rates of y- and aelimination of the deuterated and undeuterated quaternary salts in both ammonia and ammonia-d3.
Keywords: Iodide; reaction; Deuterium tracer; kinetic isotope; product composition; ammonia